Respiratory control during air-breathing exercise in humans following an 8 h exposure to hypoxia. - Herigstad, M; Fatemian, M; Robbins, P (2008)
Hypoxic exposure lasting a few hours results in an elevation of ventilation and a lowering of end-tidal P(CO2) (P(ET(CO2))) that persists on return to breathing air. We sought to determine whether this increment in ventilation is fixed (hypothesis 1), or whether it increases in proportion to the rise in metabolic rate associated with exercise (hypothesis 2). Ten subjects were studied on two separate days. On 1 day, subjects were exposed to 8h of isocapnic hypoxia (end-tidal P(O2) 55 Torr) and on the other day to 8 h of euoxia as a control. Before and 30 min after each exposure, subjects undertook an incremental exercise test. The best fit of a model for the variation in P(ET(CO2)) with metabolic rate gave a residual squared error that was approximately 20-fold less for hypothesis 2 than for hypothesis 1 (p<0.005, F-ratio test). We conclude that the alterations in respiratory control induced during early ventilatory acclimatization to hypoxia better reflect those associated with hypothesis 2 rather than hypothesis 1.